The UK higher education senior management survey: a statactivist response to managerialist governance. Issue 11 (2nd November 2021) - Erickson, Mark; Hanna, Paul; Walker, Carl
ABSTRACT: In this paper, we present results from an extensive survey of United Kingdom (UK) university academics investigating satisfaction with senior managers and university governance: the Senior Management Survey (SMS). In total, 5888 academic staff across the United Kingdom Higher Education (HE) sector completed the survey, and results were used to construct a league table of staff satisfaction with management. This table is a stark indictment of the current state of the UK HE sector, showing a mean satisfaction score of 10.54%. The SMS also collected qualitative data, and we extend the league table's insights using these data. Thematic analysis revealed seven major themes: the dominance and brutality of metrics; excessive workload; governance and accountability; perpetual change; vanity projects; the silenced academic; work and mental health. We conclude with a discussion of how this statactivist research can be used to bring about change in management and governance of UK HE.